2014
DOI: 10.1186/bcr3669
|View full text |Cite
|
Sign up to set email alerts
|

Rare key functional domain missense substitutions in MRE11A, RAD50, and NBNcontribute to breast cancer susceptibility: results from a Breast Cancer Family Registry case-control mutation-screening study

Abstract: IntroductionThe MRE11A-RAD50-Nibrin (MRN) complex plays several critical roles related to repair of DNA double-strand breaks. Inherited mutations in the three components predispose to genetic instability disorders and the MRN genes have been implicated in breast cancer susceptibility, but the underlying data are not entirely convincing. Here, we address two related questions: (1) are some rare MRN variants intermediate-risk breast cancer susceptibility alleles, and if so (2) do the MRN genes follow a BRCA1/BRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 56 publications
1
65
0
1
Order By: Relevance
“…The laboratory process has been described in detail for our recent studies of ATM, 22 CHEK2, 23 XRCC2, 24 RAD51, 25 RINT1 26 and MRN genes 27. The semi-automated approach relies on mutation scanning by high-resolution melt curve (HRM) analysis followed by direct Sanger sequencing of the individual samples for which an aberrant melt curve profile is indicative of the presence of a sequence variant.…”
Section: Methodsmentioning
confidence: 99%
“…The laboratory process has been described in detail for our recent studies of ATM, 22 CHEK2, 23 XRCC2, 24 RAD51, 25 RINT1 26 and MRN genes 27. The semi-automated approach relies on mutation scanning by high-resolution melt curve (HRM) analysis followed by direct Sanger sequencing of the individual samples for which an aberrant melt curve profile is indicative of the presence of a sequence variant.…”
Section: Methodsmentioning
confidence: 99%
“…34 More limited evidence is available for two other DNA-repair genes, MRE11A and RAD50 , which encode proteins that form an evolutionarily conserved complex with NBN . 4348 …”
Section: Evidence Of Association For Specific Genesmentioning
confidence: 99%
“…Deleterious mutations have been identified in all three genes of the MRN complex. The study done by Damiola et al, which included 1313 women < 45 years old with BC, found that rare MRN gene variants significantly contribute to early-onset BC susceptibility 112 . NBN has the strongest evidence of acting as a BC risk gene 113,114 .…”
Section: Mrn Complexmentioning
confidence: 99%